Influence of co-teaching on undergraduate student learning: A mixed-methods study in nursing - Lock, Jennifer; Rainsbury, Jacqueline; Clancy, Tracey; Rosenau, Patricia; Ferreira, Carla (Teaching and Learning Inquiry, 2018)
Co-teaching has been explored in the field of education but is a relatively new phenomenon in higher education. Its benefits and challenges are well documented; however, what is lacking is substantive evidence highlighting the influence of co-teaching amongst undergraduate students. Particularly, in practice-based professions like teaching, nursing, and social work, active participation in collaborative teams is more the norm than the exception. Undergraduate students need to have opportunities to learn how to be collaborative, as well as observe modeling of collaborative teaching practice. In the article, we report on a 2-year mixed-methods research study that investigated students’ and instructors’ experiences with co-teaching in a Nurse as Educator course. The findings from three cohorts engaged in the research suggest co-teaching to be an effective teaching and learning strategy. However, for co-teaching to be a positive experience for both students and instructors, purposeful scaffolding and supports need to be in place. Also outlined are recommendations for higher education with regard to designing and modeling co-teaching practice.